Linking Survey and Media Content Data: Opportunities, Considerations, and Pitfalls. Issue 4 (2nd October 2017) - De Vreese, Claes H.; Boukes, Mark; Schuck, Andreas; Vliegenthart, Rens; Bos, Linda; Lelkes, Yph
ABSTRACT: In media effects research a fundamental choice is often made between (field) experiments or observational studies that rely on survey data in combination with data about the information environment or media coverage. Such studies linking survey data and media content data are often dubbed "linkage studies." On the one hand, such designs are the state of the art in our field and on the other hand, they come with a long list of challenges and choices. This article reviews the rationales for linkage studies, outlines different types of linkage studies, reviews the state-of-the-art in this area, discusses which survey and content items to use in an analysis, reviews different types of analyses, outlines considerations for alternative specifications, and provides a step-by-step example.